2015
DOI: 10.1111/jicd.12189
|View full text |Cite
|
Sign up to set email alerts
|

Significant increase of oral bacteria in the early pregnancy period in Japanese women

Abstract: The data suggest that pregnancy, especially in the early periods, promotes the proliferation of microorganisms in the oral cavity and facilitates a colonization of periodontal pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(117 citation statements)
references
References 29 publications
5
102
1
9
Order By: Relevance
“…In addition, the test subjects did not present any other risk factors that could adjust the composition of the microbial flora, such as pregnancy or smoking [9, 15, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the test subjects did not present any other risk factors that could adjust the composition of the microbial flora, such as pregnancy or smoking [9, 15, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…The total cultivable microbial count, prevalence of Candida species and Staphylococcus aureus, and the proportion of counts of Candida species and S. aureus to the total cultivable microbial count were used for analysis of association of microbiota with the outcome. The methods of culture and PCR are described in Fujiwara et al [12]. For count n, log(n + 1) was used in data analyses.…”
Section: Microbial Countsmentioning
confidence: 99%
“…This was eloquently demonstrated in a recent study by Zheng et al [12] where the group found that long sea voyage sailors had reduced oral microbial diversity. Similarly, a study on the oral microbiota in early pregnant women revealed that the oral microbial counts were significantly higher in pregnant than in non-pregnant women [49]. These changes are attributed to their poor immune and general health status, suggesting the existence of a haemostasis between the oral bacterial diversity and human health.…”
Section: Resultsmentioning
confidence: 99%